2021
DOI: 10.1002/jsfa.11701
|View full text |Cite
|
Sign up to set email alerts
|

Something to chew on: technological aspects for novel snacks

Abstract: Snacks have accompanied people for a long time, meeting our needs for something fast and filling between meals. Societies and technologies have changed, and so have snacks, adapting to people's daily lives, concerns, and demands. Although traditional snacks, such as potato chips, are still ubiquitous and popular worldwide, there is not unanimity around them anymore, since many people have been looking for healthier snacks. Studies have been carried out to propose healthier snack options by changing their compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…The development of more palatable, healthier savory snacks continues to grow in response to increasing demand from consumers (Cordeiro et al., 2022 ). An exploratory study conducted in New Zealand found that nutrition is a factor considered by snack food consumers in addition to the snack's sensory properties when considering snack purchases, with sugar and fat being the two most important nutrients (Forbes et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of more palatable, healthier savory snacks continues to grow in response to increasing demand from consumers (Cordeiro et al., 2022 ). An exploratory study conducted in New Zealand found that nutrition is a factor considered by snack food consumers in addition to the snack's sensory properties when considering snack purchases, with sugar and fat being the two most important nutrients (Forbes et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A vegetable-based non-extruded snack was proposed in the present work based on avocado as matrix. A dehydration treatment was selected in order to make the avocado fruit more shelf-stable, without requiring any other preparation steps (e.g., washing, peeling, or seed removal) [ 5 ]. Avocado-based chips with and without the active extract were prepared as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The global consumption of ready-to-eat food snacks has grown in the past two decades because of radical changes in eating habits [ 4 ]. Snack food can be defined as a small portion of food eaten between regular meals [ 5 ]. According to the Snack Food Global Market Report 2023 [ 6 ], the global snack food market grew from USD 237.65 billion in 2022 to USD 256.5 billion in 2023 at a compound annual growth rate (CAGR) of 7.9%, with a post-pandemic scenario that it has promoted this situation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Snacks are defined as foods that are consumed in small quantities between meals and are mostly ready to eat. Snacking is a common social practice around the world, which has even increased after the COVID‐19 pandemic (Azeredo et al ., 2022). However, today consumers are looking for healthy snacks as a substitute for fried or high‐calorie products.…”
Section: Probiotic Fruit and Vegetable Snacksmentioning
confidence: 99%
“…Another type of non‐dairy functional food that has received special attention as potential carrier of probiotics are fruit and vegetable snacks. Snacks have the advantage of being easy to incorporate into the daily diet, generally between main meals, and their consumption has spread to all types of population from children to adults (Azeredo et al ., 2022). However, the strains used in the formulation of probiotic snacks must withstand the adverse conditions that occur both in food processing and in the gastrointestinal tract (GIT), which may limit their beneficial effect at the time of consumption (Fiocco et al ., 2019; Mbye et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%